A Comparative Look at the Duty to Mitigate Loss: the Consequences of the Violation of This Duty - Pınar Altinok Ormanci (Juridical Tribune - Review of Comparative and International Law, 2024)
The duty to mitigate loss is a general principle of law that serves to limit the liability of the party that has caused injury to the extent that the injured party has not demonstrated the diligence expected from the latter. However, this duty also serves the purpose of ensuring economic efficiency. While the classic understanding requires that, according to the principle of pacta sunt servanda, the interests of the injured party should be prioritized, today, the contract also refers to the cooperation between the parties. Therefore, reduction in the amount of claimable compensation should not be the sole sanction vis-à-vis the injured party that has violated the duty to mitigate loss. Otherwise, the injured party may escape the consequences of having violated the duty to mitigate loss by resorting to other optional rights. However, in order to ensure economic efficiency, in case the injured party violates the duty to mitigate loss, sanctions should also be foreseeable in terms of other optional rights. This study will evaluate the effect of the violation of the duty to mitigate loss in particular, with regards to request for specific performance and rescission of contract.